Melatonin interacts with repeat domain of Tau to mediate disaggregation of paired helical filaments - Balmik, Abhishek Ankur; Das, Rashmi; Dangi, Abha; Gorantla, Nalini Vijay; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Biochimica Et Biophysica Acta-General Subjects, 2020)
Tau is the major neuronal protein involved in the stabilization of microtubule assembly. In Alzheimer's disease, Tau self-assembles to form intracellular protein aggregates which are toxic to cells. Various methods have been tried and tested to restrain the aggregation of Tau. Most of the agents tested for this purpose have limitations in their effectiveness and availability to neuronal cells. We have tested melatonin, a neurohormone secreted by pineal gland and a well-known anti-oxidant, for its ability to interact with the repeat domain of Tau using ITC and NMR. In aggregation inhibition and disaggregation studies of repeat Tau, melatonin was found to modulate the aggregation propensity of repeat Tau at a concentration of 5000 mu M and was more effective in dissolving preformed aggregates rather than acting as an aggregation inhibitor. However, there were no major conformational changes in Tau in presence of melatonin as observed by CD spectroscopy. On the basis of our findings, we are proposing a mechanism by which melatonin can interact with the repeat domain of Tau and exhibit its disaggregation effect.
Keywords: Alzheimer's disease; Disaggregation; melatonin; Paired helical filaments; tau protein; Tauopathies

Macrocyclic peptides derived from AcPHF6*and AcPHF6 to selectively modulate the Tau aggregation - Dangi, Abha; Qureshi, Tazeen; Chinnathambi, Subashchandrabose; Marelli, Udaya Kiran (Bioorganic Chemistry, 2024)
Ten macrocyclic peptides, each comprising 14 amino acids, were designed and synthesized based on the Tau aggregation model hexapeptides AcPHF6* and AcPHF6. The design took into account the aggregation tendencies of each residue in AcPHF6* and AcPHF6, their aggregation models, while employing peptide-based structural design principles including N-methylation to promote turns and to block hydrogen bond propagation and elongation of the aggregation chain. NMR analysis supported that all these peptides adopted an antiparallel beta-sheet conformation. Self-aggregation studies characterized the aggregation properties of these peptides, identifying two peptides with the highest (P3) and lowest (P8) aggregation tendencies. In cross-aggregation studies with the parent peptides AcPHF6* and AcPHF6, P3 and P8 were found to promote and reduce aggregation, respectively. Furthermore, P3 and P8 demonstrated an enhancement and diminution effect on the aggregation of K18wt, indicating their capacity to modulate aggregation even at the macromolecular level. Thus, the two simple peptides, P3 and P8 selectively exhibit pro- or anti-aggregation effects on PHF peptides and Tau. This study, has thus developed structurally well-defined non-complex peptides, derived from AcPHF6* and AcPHF6, to modulate Tau aggregation as desired, offering applications in Tau model studies and the development of Tau aggregation inhibitors or promoters.
Keywords: Cyclic peptides; Peptide -based drug design (PBDD); Peptide conformation; PHF peptides; Tau Aggregation

Metal-free one-pot domino synthesis of oxazolidinethione derivatives of quaternary amino acids from α-amino esters and aldehydes using CS2 - Shinde, Dinesh R.; Krishna, Gamidi Rama; Marelli, Udaya Kiran (Journal of Organic Chemistry, 2024)
We present a streamlined, metal-free, one-pot domino approach to efficiently synthesize oxazolidinethione derivatives containing substituted quaternary amino acids. This method employs alpha-amino esters, aldehydes, and CS2 under mild conditions, constructing three new bonds (C-N, C-C, and C-O) to produce oxazolidinethione compounds featuring a quaternary center and a beta-hydroxy derivative in high yields. This scalable protocol enables the creation of libraries of biologically significant, intricate amino acid derivatives using amino esters and aldehydes.